Oran in the Roman Era: A Study of Latin Inscriptions - khatmi, mustapha (The Algerian Historical Journal, 2026)
I chose this study to explore the ancient history of the Oran region during the Roman period, a topic that has not been sufficiently addressed by historians. Despite its rich archaeological heritage, especially from the Roman era, the region remains under-researched. To investigate this subject, I focused on Latin inscriptions, which are among the most reliable historical sources. My research involved cataloging these inscriptions using archaeological data, specialized studies, and collections of Latin inscriptions. I identified 95 inscriptions across several sites in Oran, such as Portus Magnus, Ad Regiae, Portum Divinum, Castra Puerorum, Gilva Colonia, Ad Crispa, and Rass El-Aïn. This study follows a structured methodology based on translating and analyzing inscriptions while examining their historical significance. It provides insights into the political, military, social, religious, and economic aspects of Roman Oran. By offering new interpretations, this research helps bridge a crucial gap in the region’s ancient history.